Modelo Logístico para optimizar los costos del acero Crudo al ser transportado a la Empresa Ternium Colombia S.A.S (2021)
This exploration carries out logistics models to improve costs when transporting crude steel as well as raw materials from the port of Barranquilla to the company TERNIUM COLOMBIA SAS currently located in Manizales Caldas with the objective that the merchandise arrives on time. and there are no delays with loading; For this reason, the design of a logistic model was proposed to improve the costs of crude steel referring to the transport of this merchandise in TERNIUM COLOMBIA SAS of Manizales Through a descriptive exploration in which it needs a logistic model to improve its raw material and steel crude oil in order to create more supply routes since they only handle land transport. A logistics model will be carried out in order for the company to obtain routes of two types of river and rail transport so that the distribution of the load of steel and raw materials is handled more often and in this way this material is not scarce; This undertaking makes it easier to detect the insurmountable routes so that the transport of goods of the company TERNIUM COLOMBIA S.A.S is more agile and that at the same time optimizes the costs that are going to be incurred from the information of the company and the bibliography taken for its execution.